Hewn from a different kind of wood: Changes in the use of wood in the sixteenth and seventeenth centuries (Bulletin KNOB, 2015)
Long before the large-scale import of Scandinavian softwoods in the seventeenth century, deal floorboards and softwood rafters had already made their appearance before1500 and continued to appear sporadically throughout the sixteenth century, especially in cities situated on or close to the sea. The boards in that period were quite substantial: 30-50 centimetres wide and 2.7 centimetres thick. With the supply of oak via the occupied eastern and southern parts of the country wholly or partially halted during the Eighty Years’ War, alternatives were sought and were found primarily in softwood from Scandinavia. The Twelve Years’ Truce saw an explosive growth in imported softwood, but also a brief and final resurgence in the import of highquality oak from Germany. But even before that time, at the beginning of the Eighty Years’ War, there had been instances of single floor frames constructed in softwood.In the South, the River Maas had always been an important supply route for oak. After the Eighty Years’ War trade between the Netherlands and Germany via the Rhine resumed, while timber supplies from Norway were hampered by competition from England. This no doubt boosted the supply of softwood from the basins of the large northern rivers and the Baltic. Throughout the seventeenth century oak continued to be used for special features such as interior woodwork and frames, but over the course of the eighteenth century softwood became the most widely used construction timber.